Using storybooks to enhance health awareness among schoolchildren at risk of tuberculosis - Yuniske Penyami; Moh Projo Angkasa; Sumarni Sumarni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: In 2020, Indonesia ranked third globally for the highest number of tuberculosis (TB) cases, with an estimated 969,000 cases. In 2022, Pekalongan recorded 150 pediatric TB cases, with many contacts refusing TB preventive therapy. Children living in the same household as adults with positive acid-fast bacilli (AFB) TB are at high risk of contracting Mycobacterium tuberculosis. One preventive measure is introducing age-appropriate education to enhance their understanding. Purpose: To examine the impact of education through storybook media on tuberculosis awareness among school-aged children living with TB patients. Method: A quasi-experimental one-group pretest-posttest design. Using purposive sampling, 30 children who shared a household with TB patients participated. They received health education interventions through storybooks and leaflets. A TB knowledge questionnaire and an observation sheet for cough etiquette practices were used as research instruments. Results: There was a significant improvement in children’s knowledge and cough etiquette practices after receiving health education through storybooks and leaflets, as demonstrated by the Wilcoxon test (p-value < 0.05). Conclusion: Health education using storybooks effectively enhances knowledge and improves cough etiquette skills in school-aged children.